Dynamic communication performance of a modified hierarchical 3D-Torus network under non-uniform traffic patterns - Rahman, M.M. Hafizur; Sato, Yukinori; Inoguchi, Yasushi (2010)
A Modified Hierarchical 3D-Torus (MH3DT) network is a 3D-torus network of multiple basic modules, in which the basic modules are themselves 3D-torus networks which are hierarchically interconnected into higher-level networks. The static network performance of the MH3DT has already been studied and has been shown to be good. Dynamic communication performance has been evaluated using dimension-order routing and 2 virtual channels under uniform traffic patterns but not under non-uniform traffic patterns. In this paper, we evaluate the dynamic communication performance of MH3DT under five non-uniform traffic patterns, and compare it with other networks. We found that under non-uniform traffic patterns, the MH3DT yields high throughput and low latency, providing better dynamic communication performance compared to H3DT, TESH, mesh, and torus networks. Also, we found that non-uniform traffic patterns have higher throughput than uniform traffic patterns in the MH3DT network.